PENGUKURAN RISIKO KURANG ENERGI KRONIS DAN EDUKASI GIZI PADA REMAJA PUTRI DI SMA NEGERI 15 KEC. MESTONG KAB. MUARO JAMBI - Kalsum, Ummi; Sitanggang, Hendra Dhermawan; Fitri, Adelina (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
The incidence of stunting in toddlers is influenced by the health of mothers and prospective mothers (adolescent girls) who are vulnerable groups, especially Chronic Energy Deficiency (CHD). SEZ is still commonly found in women of childbearing age (WUS) and adolescent girls. SMA Negeri 15 Muaro Jambi Regency is located in Mestong District, including rural areas with high stunting rates. This community service was carried out in May-July 2023 with stages, advocay, socialization, nutrition education and measurement of nutritional status (upper arm circumference, weight and height) in 10th and 11th grade adolescent girls totaling 71 people. There are still many students who are at risk of SEZ due to Upper Arm Circumference (LiLA) < 23.5 cm by 43.1%. Quantitative assessment was conducted pre and post-test before and after nutrition education. The average value of knowledge score before education was 4.54 and increased to 7.58 during the post test. The results of the Wilcoxon Test analysis found a value of P = 0.0001 which means that there is an effect of providing nutrition education to adolescent girls at SMA Negeri 15 Muaro Jambi Regency. Providing education about the risk of chronic energy deficiency and anemia has an influence on the level of knowledge of adolescent girls at SMA Negeri 15 Muaro Jambi. It is recommended to apply a balanced nutritional diet and take LiLA measurements in order to prevent SEZ and Anemia.